Victims of cyberviolence: forms, prevalence and gender differences - Barrera-Mesa, Carmen Emilce; Caro-Caro, Edgar Orlando; Del Rey-Alamillo, Rosario (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The objective of this research is to analyze cyber-victimization in school adolescents, through a descriptive study in a sample of 656 elementary and middle school students from a Colombian educational institution, to whom the Questionnaire on Cyber-victimization in High School Students was applied. The results show that 63.41% of the students state that they have suffered cyber-victimization, occurring to a greater extent in those who do not identify with either of the two genders, followed by the male and female genders, respectively. Regarding the types of cyber-victimization, the sexual one is presented to a greater extent, suffered mainly by girls, followed by online exclusion, present mostly in boys, and verbal-written cyber-victimization, which is presented to the same extent in both genders. It is concluded that it is necessary to establish strategies that contribute to improving coexistence in virtual spaces frequented by Colombian schoolchildren.